Pemberdayaan Pemuda Desa Jatitamban melalui Budidaya Maggot: Solusi Edukatif dan Berkelanjutan dalam Pengelolaan Sampah Organik - Deni Achmad Syafi’i; Lila Aisyah; Dila Adelia Juliarti; Anita Alviyani; Jermia Edonie; Nor Sriwahyuni; Danang Aditya Firmansyah; Faiq Samsul Huda; Aura Bintang Arvisyah; Muhammad Muhyidin; Siti Aisyah Wardhania Hamidah; Dininiar Ratna Dewanti (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
The problem of organic waste remains a serious issue in Indonesia, including in rural areas. Jatitamban Village, Bondowoso Regency, faces similar challenges due to household waste and residual by-products from local small enterprises producing tape and cassava chips, which are not yet optimally managed. The Community Service Program (KKN) of the University of Jember implemented an initiative to empower village youth through maggot cultivation as an environmentally friendly and economically valuable solution for organic waste management. This study employed a Community-Based Research (CBR) approach by engaging local youth as active partners in every stage of the program, including observation, planning, socialization, technical training, workshops, and monitoring. The results indicate that Black Soldier Fly (BSF) maggot cultivation serves as an effective strategy to reduce the volume of organic waste while producing value-added products such as alternative animal feed and organic fertilizer. The involvement of youth not only enhanced their knowledge and skills but also fostered environmental awareness and created new entrepreneurial opportunities. Furthermore, the program successfully established a solid and independent youth group capable of sustainably managing organic waste through maggot cultivation practices. The implications of this program extend beyond environmental improvement to promoting village economic independence through the utilization of organic waste. Therefore, youth empowerment through maggot cultivation can serve as a strategic model for sustainable waste management as well as strengthening community capacity in rural areas.